Binge Watching Platform Video on Demand: Generasi Z dan Hubungannya dengan Fear of Missing Out - Guinea Utami; Danny Sanjaya Arfensia; M. Hanif Musthofa; Yudi Mahlil (Program Studi Psikologi, Fakultas Kedokteran, Universitas Syiah Kuala, 2025)
Technological developments have changed habits in watching television, it rise up to the phenomenon of binge watching which is watching several episodes of a series at once. Television which previously could only be accessed offline, nowadays can be accessed online via Video on Demand (VoD) services. Most VoD service users are generation Z and are likely to be affected by Fear of Missing Out (FoMO) namely the fear of losing information about a series or film that is being discussed by other people. The aim of this research is to determine the relationship between binge watching video on demand and FoMO in generation Z. This research uses a quantitative approach with a purposive sampling technique. The research subjects were 280 respondents with an age range of 29-21 years and came from various provinces in Indonesia. Data collection in this study used the adaptation measuring tools Binge-Watching Engagement and Symptoms Questionnaire (BWESQ) and Fear of Missing Out Scale (FoMOS). Data analysis using Pearson Correlation shows a significant value of p=0.0010.05 with a correlation (r) of 0.456 which shows that there is a significant relationship between Binge Watching and FoMO.Perkembangan teknologi mengubah kebiasaan dalam menonton televisi sehingga memunculkan fenomena binge watching yaitu menonton beberapa episode serial sekaligus. Televisi yang dulunya hanya dapat diakses secara offline, kini dapat diakses secara online melalui layanan Video on Demand (VoD). Sebagian besar pengguna layanan VoD adalah generasi Z dan berkemungkinan terdampak Fear of Missing Out (FoMO) yaitu takut kehilangan informasi mengenai serial atau film yang sedang didiskusikan oleh orang lain. Tujuan dari penelitian ini adalah untuk mengetahui hubungan binge watching video on demand dengan FoMO pada generasi Z. Penelitian ini menggunakan pendekatan kuantitatif dengan teknik purposive sampling. Subjek penelitian berjumlah 280 responden dengan rentang usia 29-21 tahun dan berasal dari berbagai provinsi di Indonesia. Pengumpulan data dalam penelitian ini menggunakan alat ukur adaptasi Binge-Watching Engagement and Symptoms Questionnaire (BWESQ) dan Fear of Missing Out Scale (FoMOS). Analisis data menggunakan korelasi Pearson menunjukkan nilai signifikansi p=0,0010,05 dengan korelasi (r) 0,456 yang menunjukkan bahwa terdapat hubungan yang signifikan antara binge watching dan FoMO.